Evolution of Cranial Ontogeny in South American Canids (Carnivora: Canidae) - Segura Gago, Alda Valentina; Cassini, Guillermo Hernán; Prevosti, Francisco Juan (Evolutionary Biology)
South American Canids are endemic and form a monophyletic clade supported by molecular and morphological data, with the exception of Urocyon cinereoargenteus, which is a typical North American form. South American canids occur in almost all environments in continent, and exhibit diet diversity and large size variation. Here we analyzed the skull ontogeny by applying 3D geometric morphometric techniques, in a well-represented sample of South American canids, with the aim of exploring variation in cranial size and shape as well as evolutionary patterns of such variation. The sample consisted of 1227 crania of the 11 living species of South American canids and 92 crania of Canis lupus and Vulpes vulpes, which were considered as out-groups. South American canids exhibited similar shape and diet (they are mostly omnivorous), which implies similar mechanical commitments, which are reflected in their almost uniform skulls. However, it is possible that cranial similarity is related to a shared evolutionary history with a short time of divergence. Speothos venaticus differed in its ontogenetic trajectory, with the difference being stronger between adults of this species and the remaining canids. The skull configuration is consistent with the hyper-carnivorous diet. In the case of Chrysocyon brachyurus, size plays an important role in the structure of a skull, giving rise to remarkable morphological differences from other species, although in terminal stages of its ontogeny. Fil: Segura Gago, Alda Valentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico - Tucumán. Unidad Ejecutora Lillo; Argentina. Fundación Miguel Lillo; Argentina Fil: Cassini, Guillermo Hernán. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino ...